2006
DOI: 10.1177/117727190600100004
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need Biomarkers for Disc Degeneration?

Abstract: Disc degeneration plays a major role in this country’s medical, social and economic structure. The life-time prevalence of low back pain, which has disc degeneration as its cause, is about 80% in the general population. It is a primary cause of disability and estimated costs related to low back disorders exceed $100 billion per year in the U.S. alone. Biomarkers are becoming increasingly important as indicators of the presence of disease, and in evaluating outcomes during clinical treatment. Cell-based biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…A recent review of the literature indicates several serum and urine biomarkers may be useful in understanding the etiology of knee and hip OA [51]. Gruber and Hanley [52] indicated that biological markers for intervertebral disc degeneration that could be used to correlate patients’ status regarding pain and symptoms would be especially meaningful. Minimum work has been performed on this topic, but a few small studies of select samples have found associations between DSN and C-terminal cross-linked telopeptide (CTX-II), a biomarker of type II collagen degradation [53, 54].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…A recent review of the literature indicates several serum and urine biomarkers may be useful in understanding the etiology of knee and hip OA [51]. Gruber and Hanley [52] indicated that biological markers for intervertebral disc degeneration that could be used to correlate patients’ status regarding pain and symptoms would be especially meaningful. Minimum work has been performed on this topic, but a few small studies of select samples have found associations between DSN and C-terminal cross-linked telopeptide (CTX-II), a biomarker of type II collagen degradation [53, 54].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…During degeneration, the IVD becomes dehydrated and vascularized, and there is an ingrowth of nerves (Hughes et al , 2012). As a multi-factorial process, disc degeneration is influenced by factors such as genetic predisposition, lifestyle conditions, including obesity, occupation, smoking and alcohol consumption (Samartzis et al , 2012), aging phenomena (Gruber and Hanley, 2007) and other health factors, such as diabetes. Disc degeneration is important clinically because of a strong association between disc degeneration and back pain (Luoma et al , 2000), which is a major public health problem in modern industrialized societies.…”
Section: Introductionmentioning
confidence: 99%
“…IDD is a complex and multi-factorial process that is influenced by genetic predispositions, aging, biomechanical loading and physical activities, lifestyle and other health-associated factors, including diabetes ( 43 ). Numerous clinical investigations have indicated that cell-based biological therapies, including disc cell augmentation, application of growth factors/cytokines and gene therapy, may be employed for the treatment of IDD ( 44 , 45 ). The development of biomarkers for IDD is valuable in the early stages of disc degeneration ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical investigations have indicated that cell-based biological therapies, including disc cell augmentation, application of growth factors/cytokines and gene therapy, may be employed for the treatment of IDD ( 44 , 45 ). The development of biomarkers for IDD is valuable in the early stages of disc degeneration ( 45 ). lncRNAs have been implicated in multiple pathological processes of IDD ( 46 ), and lncRNAs and DEGs in patients with disc degeneration may have potential as diagnostic or prognostic biomarkers ( 47 ).…”
Section: Discussionmentioning
confidence: 99%